Boundary layer flow of williamson hybrid ferrofluid over a permeable stretching sheet with thermal radiation effects - Wan Rosli, Wan Muhammad Hilmi; Mohamed, Muhammad Khairul Anuar; Md Sarif, Norhafizah; Mohammad, Nurul Farahain; Soid, Siti Khuzaimah (Penerbit Akademia Baru, 2023)
This research investigated the convective boundary layer flow and heat transfer of Williamson hybrid ferrofluid over a permeable stretching sheet with thermal radiation effects. Human blood is employed as a based fluid while magnetite (Fe3O4) and copper (Cu) are taken as the hybrid ferroparticle. The study started with transforming the nonlinear partial differential equation system that governed the model to a more convenience non-linear dimensionless ordinary differential equations using the similarity transformation. The transformed equations obtained then are solved numerically using the Runge-Kutta-Fehlberg (RKF45) method in Maple software. The characteristics and effects of stretching parameter, permeability parameter, thermal radiation parameter as well as the ferroparticle volume fraction in the Williamson hybrid ferrofluid towards the temperature profiles, velocity profiles as well as the Nusselt number and the skin friction coefficient are analysed and discussed. The result of this research for various pertinent parameter varies differently. It can be concluded that the increase in magnetic parameter, the Williamson parameter, the stretching parameter, and the permeability rate parameter increase the skin friction and reduced the velocity profile. Furthermore, the increase in stretching parameter, thermal radiation parameter and the permeability rate results to the increase in the Nusselt number.